Tea tree essential oil and the treatment of vulvovaginal candidiasis: Knowledge and use by nurses (Research, Society and Development, 2023)
Tea tree oil is an essential oil used in aromatherapy, which consists of the use of volatile concentrates extracted from plants. It is a therapeutic resource and an expanding area of ​​care for nursing. This is a descriptive, population-based, cross-sectional, quantitative research, which aims to identify nurses' knowledge about aromatherapy and the use of tea tree oil in the treatment of vulvovaginal candidiasis and also identify whether they are interested in insert complementary therapies into the nursing consultation. Data were collected using the snowball method and data analysis using descriptive statistics. The data collection procedures were approved by the Research Ethics Committee of the Universidade Regional Integrada do Alto Uruguai e das Missões – Campus de Santo Ângelo by opinion no. 4,928,596. The environment for data collection was virtual, where data collection began on the first of September 2021 and ended 30 days after its opening. The sample consisted of 73 participants (n=73). The majority of participants (86.3%) are aware of the National Policy on Integrative and Complementary Practices and 98.6% have heard about aromatherapy and essential oils, however, few have already taken a training course in aromatherapy (20.5%). Even though there is a lack of knowledge of the policy and aromatherapy on the part of the participating nurses, in addition to little provision in the services, it was found that there is an interest in training and implementation in the services.